Implementasi Metode Active Learning dalam Pembelajaran Aqidah Akhlak di MA Ma’arif NU Sains Al-Qur’an Sumbang Banyumas - Agustin, Aulia; Hidayat, Fahri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Improving the quality of learning requires teachers to choose methods that encourage active student participation, one of which is through an active learning approach. This study aims to describe the implementation of the active learning method in learning Aqidah Akhlak at MA Ma'arif NU Sains Al-Qur'an Sumbang Banyumas. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the active learning method is implemented through several strategies such as discussion, question and answer, and peer teaching, which are carried out in stages starting from problem identification, asking questions, planning and implementing investigations, data analysis, drawing conclusions, to presenting results. The implementation of this method has been proven to be able to increase students' activeness, understanding, and critical thinking skills. Despite obstacles such as differences in student abilities, limited time, and limited facilities, teachers are able to overcome these through guidance and motivation to students.